Regulatory Models for IP Protection of Crafts and Folk Art: Insights from Indonesia and Vietnam - Agustianto Agustianto; Intan Triana Putri; Hari Sutra Disemadi; Dwi Fidhayanti; Ratih Anggraini (Syura: Journal of Law, 2026)
The cultural uniqueness of each country is a key driver of tourism development, including through the strengthening of creative cities within the UNESCO Creative Cities Network (UCCN). Indonesia and Vietnam are closely linked in this regard, as both have member cities in the Crafts and Folk Art category. However, the regulatory frameworks for the protection of crafts and folk art in the two countries differ in their structure and degree of normative clarity. This study aims to analyse the similarities and differences in the regulation of copyright, related rights, and geographical indications in Indonesia and Vietnam using Gustav Radbruch’s theory of legal certainty, and to formulate directions for strengthening Indonesia’s legal framework through the responsive law theory of Philippe Nonet and Philip Selznick. This research employs a normative legal method with statute and comparative approaches, relying on library research analysed qualitatively and descriptively. The study finds that although Indonesia and Vietnam both provide legal bases for IP protection of crafts and folk art, Vietnam offers a higher level of certainty regarding protected objects and clearer norms by integrating copyright, related rights, and geographical indications within a single Vietnam IP Law framework, whereas Indonesia’s provisions remain fragmented across several regimes and therefore require further harmonisation. The study also underscores the significance of a responsive law approach, operationalised through the regulatory design delivery inspection model, to connect IP protection, UCCN status, and sustainable creative tourism in Indonesia, so that legal protection becomes not merely formal but genuinely strengthens cultural authenticity and ensures fair economic benefits for cultural bearer communities.